Screening for Diabetes Mellitus among Tuberculosis Patients: Findings from a Study at a Tertiary Hospital in Lusaka, Zambia - Fwoloshi, Sombo (Can J Infect Dis Med Microbiol, 2018)
BACKGROUND: Diabetes mellitus (DM) is known to be associated with active tuberculosis (TB). Zambia is a low-income sub-Saharan African country with a high TB burden and increasing numbers of newly diagnosed DM patients. MATERIALS AND METHODS: This was an observational study conducted at the University Teaching Hospital in Lusaka, Zambia, from October 2014 to February 2016. Adult patients with active TB were screened for DM. RESULTS: A total of 127 individuals were enrolled in the study. Six patients (5%) were found to have diabetes. Of these, three had a prior diagnosis of diabetes and were on medication while three were newly diagnosed. Low education level was significantly associated with DM (p=0.001; 95% CI 0.001–0.148). CONCLUSION: The prevalence of DM among individuals with smear positive TB in our study population was similar to that of the general population in Zambia.